New methodology of dynamical material response of dissimilar FSWed Al alloy joint under high strain rate laser shock loading. (October 2022) - Ayad, Mohammad; Lapostolle, Lucas; Rondepierre, Alexandre; Bras, Corentin Le; Ünaldi, Selen; Donik, Črtomir; Klobčar, Damjan; Berthe, Laurent; Trdan, Uroš
Graphical abstract: Highlights: New methodology of material characterization in high strain rate regime. Successful distinction between material planes and its properties. Perfect correlation between grain size, residual stresses and J-C parameters. Prediction of material behaviour under dynamic loading. Abstract: This paper presents an innovative methodology of material characterization under high strain rate (order of 10 7 s - 1 ) laser shock loading coupled with microstructural and mechanical material features. To that scope, experimental and simulation analyses have been conducted for Al alloys (AA7075-T6 and AA2017-T4) and dissimilar Friction Stir Welded (FSWed) AA7075-AA2017 joint, under shock pressure of 4.5 GPa (laser power density of 3.5 GW / cm 2 ). In order to perform proper in-depth material model simulation of these alloys and dissimilar pairs, Johnson–Cook (J-C) material model has been coupled with Grüneisen equation of state using the non-linear explicit code LS-DYNA. For the first time, we provided a way to differentiate between material behaviour in the cross-section and the in-plane rolling and welding direction. What is more, we have provided the link between microstructural features and mechanical properties such as microhardness, residual stresses and the identified material parameters. By achieving this goal, the bigger difference between studied planes was confirmed for strain hardening modulus, strain hardening exponent and strain rate sensitivity parameters. Obtained results and proposed methodology indicate high potential to predict material properties and behaviour of dynamically stressed parts and at the same time can be used for optimization of LSP process.